2019
DOI: 10.31557/apjcp.2019.20.9.2619
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combination of Steroid and L-Asparaginase on Hyperglycemia in Children with Acute Lymphoblastic Leukemia (ALL)

Abstract: between age 2-6 years old (Hunger et al., 2012). Mostert et al., (2006) reported that, out of all of the children suffering from ALL in Yogyakarta, 35% refused medication, 23% died of medication-associated causes, 22% had their conditionworsened or experienced relapse and 20% had 5-years event-free survival (EFS). Regardless of significantly better prognosis, EFS, and overall survival (OS) with risk-based stratification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…14 A study reported that the incidence of hyperglycemia as a side effect of steroid and L-Asp combination was 5.2%, from three centers in Indonesia. 15 We found that 6 subjects (16.6%) experienced hyperglycemia when they received prednisone as well as L-Asp simultaneously during the induction phase, with fasting BG ranging from 130 mg/dL to 311 mg/dL , and 329 mg/dL in one episode of two-hour postprandial BG. Native L-Asp, on the contrary, was reported to result in more hypoglycemia than hyperglycemia during chemotherapy in childhood ALL.…”
Section: Discussionmentioning
confidence: 76%
“…14 A study reported that the incidence of hyperglycemia as a side effect of steroid and L-Asp combination was 5.2%, from three centers in Indonesia. 15 We found that 6 subjects (16.6%) experienced hyperglycemia when they received prednisone as well as L-Asp simultaneously during the induction phase, with fasting BG ranging from 130 mg/dL to 311 mg/dL , and 329 mg/dL in one episode of two-hour postprandial BG. Native L-Asp, on the contrary, was reported to result in more hypoglycemia than hyperglycemia during chemotherapy in childhood ALL.…”
Section: Discussionmentioning
confidence: 76%
“…In the study by Aisyi et al only 5.2% of the respondents were diagnosed with hyperglycemia caused by dexamethasone in combination with L-asparaginase [16].…”
Section: Adherence To Dietary Recommendations By Children and Adolescmentioning
confidence: 92%
“…W badaniu przeprowadzonym przez Aisyi i wsp. tylko 5,2% badanych miało stwierdzoną hiperglikemię spowodowaną przez deksametazon w połączeniu z L-asparaginazą [16].…”
Section: Dyskusjaunclassified
“…GIH is a phenomenon that typically occurs acutely with initiation[ 85 , 87 , 90 , 91 ], and hyperglycemia was found to be significant by day 2 in those being treated systemically for hematologic malignancies[ 11 ]. The degree of glucose elevations range widely and are most frequently modest (< 14 mmol/L)[ 92 ], nonetheless severe hyperglycemia (> 28 mmol/L) and DKA have also been reported[ 11 , 93 ], with rare reports of hyperglycemic hyperosmolar syndrome as well[ 94 ]. Other AE associated with GIH range from mild to serious, such as increased infections and lengthened of hospital stays[ 11 , 16 , 86 , 95 - 98 ].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Prednisone levels peak 4-8 h after ingestion and its duration of action is between 12 h to 16 h; these pharmacokinetics correlated with increases in postprandial glucose in the afternoon and evening when administered in the morning[ 11 , 87 , 92 ]. During induction therapy for acute lymphoblastic leukemia the use of long-lasting dexamethasone was linked with a significant increase in risk of GIH when compared to those prescribed the intermediate-acting prednisone[ 93 ]. In contrast, a comparison between dexamethasone 8-12mg IV and prednisone 40mg orally found extensive hyperglycemia in the majority of all patients, without differences between the two therapies[ 94 ].…”
Section: Glucocorticoidsmentioning
confidence: 99%